Power, politics, and the cults of Isis : proceedings of the Vth International Conference of Isis studies, Boulogne-sur-Mer, October 13-15, 2011 - Bricault, Laurent. (Religions in the Graeco-Roman World, 2014)
In the Hellenistic and Roman world intimate relations existed between those holding power and the cults of Isis. This book is the first to chart these various appropriations over time within a comparative perspective. Ten carefully selected case studies show that "the Egyptian gods" were no exotic outsiders to the Hellenistic and Roman Mediterranean, but constituted a well institutionalised and frequently used religious option. Ranging from the early Ptolemies and Seleucids to late Antiquity, the case studies illustrate how much symbolic meaning was made with the cults of Isis by kings, emperors, cities and elites. Three articles introduce the theme of Isis and the longue durée theoretically, simultaneously exploring a new approach towards concepts like ruler cult and Religionspolitik .